2001
DOI: 10.2136/sssaj2001.6551508x
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of Rare Earth Oxides as Tracers for Soil Erosion and Aggregation Studies

Abstract: Most existing soil loss data are spatially‐averaged, though various tracing techniques have been used for obtaining spatially‐distributed data. Spatially‐distributed soil erosion data are needed for validating physically‐based erosion prediction models and for better understanding soil erosion dynamics. The objectives of this study were to evaluate the feasibility of using rare earth element (REE) oxides directly as tracers for soil erosion studies by examining their binding ability with soil materials, and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 19 publications
4
107
0
5
Order By: Relevance
“…The results showed that Ce migrated downward approximately 1 cm every year in acid soils, 0.2 cm in neutral soils, and almost none in alkaline soils. Zhang et al (2001) investigated Ce and Nd transport characteristics with the leaching experiment of soil columns, and it was found that even if the REEs amount reached 50% of the desorption rate of surface soils and the rainfall amount in the simulated rainfall experiments reached 1,000 mm, in most cases the migration depth of Ce and Nd was within 4 cm in nine different kinds of soils. In a few cases, the REEs were leached to a depth of 10 cm, but no 141 Ce and 147 Nd were detected in the leachate.…”
Section: Effects Of Soil Type On Vertical Leaching Of Rees and Pmentioning
confidence: 99%
“…The results showed that Ce migrated downward approximately 1 cm every year in acid soils, 0.2 cm in neutral soils, and almost none in alkaline soils. Zhang et al (2001) investigated Ce and Nd transport characteristics with the leaching experiment of soil columns, and it was found that even if the REEs amount reached 50% of the desorption rate of surface soils and the rainfall amount in the simulated rainfall experiments reached 1,000 mm, in most cases the migration depth of Ce and Nd was within 4 cm in nine different kinds of soils. In a few cases, the REEs were leached to a depth of 10 cm, but no 141 Ce and 147 Nd were detected in the leachate.…”
Section: Effects Of Soil Type On Vertical Leaching Of Rees and Pmentioning
confidence: 99%
“…The REO tracers used for the car park, roof and road were Nd, Sm, Gd, Tb; Y, La, Ce, Pr; Dy, Ho, Er, Yb, respectively. The sediment was tagged following the detailed methodology described by Zhang et al (2001Zhang et al ( , 2003, at a tracer concentration rate of 10 g/kg of sediment (Allen et al 2015), and released evenly onto the urban surfaces only once at the beginning of the sampling period. Tagged sediment was designed to mimic naturally occurring urban sediment pollution, in both mass and particle size distribution (PSD).…”
Section: Methodsmentioning
confidence: 99%
“…Esta técnica é especialmente notável pela alta especificidade e sensibilidade, como pode-se observar no trabalho de revisão deste tema de Bonardi e colaboradores. 78 A utilização de traçadores radioativos também tem fornecido imensa contribuição para o estudo de processos ambientais, tais como o estudo dos processos de erosão, 82 7 Be meia vida de 53 dias, são formados naturalmente na atmosfera e depositados na superfície por precipitação, distribuindo-se em diferentes profundidades do solo. Esses dois elementos, quando utilizados em conjunto como traçadores, fornecem uma identificação mais precisa do processo de erosão nos rios.…”
Section: Traçadores Radioativosunclassified